THE INFLUENCE OF HEALTH PROMOTION USING AUDIO VISUAL MEDIA ON INCREASING STUDENTS' ORAL HEALTH KNOWLEDGE AT SDI KAMPUS UNHAS 1 - Abdi, Muhammad Jayadi; Anas, Risnayanti; Romadhan, Rezky Rahmat (Universitas Baiturrahmah, 2024)
Introduction: Dental and oral health problems are a major problem in school-aged children. Nearly a third of Indonesia's population has dental and oral health problems. Efforts that can increase knowledge about dental and oral health are through health promotion using audio-visual media, counseling using creative media encourage students to study hard and optimally received the lesson. Objective: To determine the influence of health promotion using audio visual media in increasing dental and oral health knowledge of SDI students. Method: This type of research was a quasi-experiment with a pre-test and post-test group design and analysis using the Wilxocon test with a sample size about 48 students. Results: Based on the results of research entitled The Influence of Health Promotion Using Audio Visual Media in Increasing Knowledge of Dental and Oral Health at SDI Kampus 1 UNHAS. Based on a comparison using the Wilcoxon test, a p-value of 0.000 was obtained, namely less than 0.05 (p value <0.05) . This shows that the treatment given, namely Audio Visual Media, increases students' knowledge about dental and oral health after it is applied. Conclusion: There is any influence of increasing knowledge on health promotion using audio-visual media.